HUBUNGAN JARAK DAN SANITASI KANDANG DENGAN KEBERADAAN BAKTERI COLIFORM AIR SUMUR DI DESA BANGKAHAN KECAMATAN KAMPUNG MELAYU KOTA BENGKULU - Hasan Husin; Riski Wais Al Qorni; Sarkawi Sarkawi; Agus Ramon; Emi Kosvianti (Avicenna: Jurnal Ilmiah, 2022)
ABSTRACT Dug wells are a means of providing clean water that is always used by the community, dug wells are very easily polluted due to seepage from animal waste disposal sites. The presence of bacteria in well water is an indication of bacteriology. The purpose of this study was to determine the relationship between the distance of cattle pens, sanitation of livestock pens, and the bacteriological quality of community dug well water in Bangkahan Village, Kampung Melayu District, Bengkulu City in 2022. This type of research used a cross sectional correlation study to see the relationship between cage spacing, cage sanitation on coliform bacteria in dug well water. The number of population in the study was 17, purposive sampling using the Slovin formula from 15 samples taken 7 dug wells. Measurement of cage distance using a meter, bacteriological testing of well water in the laboratory. The results showed that 7 samples of dug wells were examined, 6 dug wells were contaminated with coliform bacteria. The results of the correlation test showed that there was a relationship between the distance between the cage and the coliform bacteria in dug wells, a value of 0.864, that the relationship between the two variables was very strong, and the sanitation of the cage with coliform bacteria in well water had no relationship with a value of 0.215. The relationship between the two variables was low. It is recommended to the Health Office to conduct counseling to the people of Bangkahan Village about the distance of the cages that meet the requirements and always carry out bacteriological examinations of well water. Keywords: Distance, Sanitation, Coliform Bacteria